Optimization and Characterization Study of Preparation Factors of Activated Carbon Derived from Coconut shell to Remove of H2S from Wastewater - Habeeb, Omar Abed; K., Ramesh; Sethupathi, Sumathi; R. M., Yunus (Ideal International E-Publication, 2017)
The main point of this work is to investigate the preparations variables of activated carbon derived from coconut shell (CSAC) for removal of hydrogen sulfide (H2S) from wastewater. The CSAC was chemically modified with potassium hydroxide (KOH). The central composite design (CCD) under response surface methodology (RSM) was employed to prepare the CSAC. The three preparation variables impact on the removal efficiency (%) of H2S were examined. The preparation parameters to the responses were correlated by developing a quadratic model. The analysis of variance shows the significant impact of variable on each experimental design responses. The results show that the temperature of 857◦C, chemical impregnation ratio of 3.4wt% and activation time of 66 min were the optimum conditions for CSAC preparation of with removal efficiency of 88.8%.